Efektivitas Media Peraga Pembelajaran Virus Covid-19 Berbahan Dasar Limbah Plastik Pada Sekolah Terdepan, Terluar, Dan Tertinggal Mts Lkmd Wanusia Taa Desa Taa Kecematan Kilmury Kabupaten Seram Bagian Timur - Watimury, Pebry (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
The media or learning resources are helpful tools in teaching learning activities. These tools or media can help solve students' difficulties in understanding concepts and can also produce feedback from students that triggers the student's motivations, interests and good knowledge. The learning media used on the covid-19 virus study of the outermost and lags students is a form of improvement and The quality of studying at school. The goal of this assessment is to know how effective the application of the covid-19 virus study is based on plastic waste at the top of the school, outlying and lagging MTS taa village TAA kilmuri regency, This type of study is a quantitative experiment quasi ation that is, by collecting efficacy data from sample control groups and experiment groups. The results of the study on the control class of 15 total students are not complete in learning, on the VIII two experiment class with the number of 15 students all meet graduation standards, on the motivation to study, knowledge is good and craft, students are on a predicate of good and excellent. The conclusion of this study, with the media studying the covid-19 virus based on plastic waste on top school students, outer and backward make the motivation, skill and good knowledge of the average student fall into an excellent category with the results above the established value standard. Keywords: Visual Media; Covid-19 Virus, 3T